ECONOMIC VIABILITY AND SELECTION OF IRRIGATION SYSTEMS USING SIMULATION AND STOCHASTIC DOMINANCE - Duenhas, Luiza Helena; Saad, João Carlos Cury (IRRIGA, 2009)
ECONOMIC VIABILITY AND SELECTION OF IRRIGATION SYSTEMS USING SIMULATION AND STOCHASTIC DOMINANCE Luiza Helena Duenhas1 ; João Carlos Cury Saad2 1Conselho Nacional de Desenvolvimento Científico e Tecnológico, Brasília, DF, luizad@cnpq.br 2Departamento de Engenharia Rural, Faculdade de Ciências Agronômicas, Universidade Estadual Paulista, Botucatu, SP 1 SUMMARY In humid areas, irrigation systems are used to increase the crop yield. The selection of irrigation system to be used is a decision made under uncertainty. This paper shows a procedure that is an association betweenMonte Carlosimulation method and the criterion of Stochastic Dominance to analyze the viability and identify the best economic option under risk condition. To illustrate the applicability of the procedure, three types of irrigation systems are evaluated to be used in a citrus orchard inSao Paulo State,Brazil. The irrigation systems evaluated are: drip, microirrigation, and traveling sprinkler. The decision indicator is the present value of net benefit associated with the increase of yield obtained with the irrigation system adopted. TheMonte Carlosimulation method is used to generate the cumulative distribution of the present value for each one of the irrigation systems. These curves allow to analyze the economic viability of the three irrigation systems. According to the First Degree Stochastic Dominance, traveling sprinkler system was the best alternative with 95.7% probability of obtaining a positive present value. The second best option was the microirrigation with 82.7% and the worst result (57.3%) was obtained with drip irrigation. KEYWORDS: Economic viability, simulation, irrigation systems, stochastic dominance, citrus. 1DUENHAS, L. H. ; 2SAAD, J. C. C. VIABILIDADE ECONÔMICA E SELEÇÃO DE SISTEMAS DE IRRIGAÇÃO UTILIZANDO SIMULAÇÃO E DOMINÂNCIA ESTOCÁSTICA 2 RESUMO Em regiões úmidas, sistemas de irrigação são utilizados para aumentar a produtividade das culturas. A escolha do sistema de irrigação a ser utilizado é uma decisão feita sob incertezas. Este trabalho apresenta um procedimento que associa o método de simulação de Monte Carlos e o critério de Dominância Estocástica para analisar a viabilidade e identificar a melhor opção econômica sob condição de risco. Para exemplificar a aplicabilidade do procedimento, três sistemas de irrigação são avaliados para uso em pomar de citros no Estado de São Paulo, Brasil. Os sistemas de irrigação avaliados são: gotejamento, microaspersão e autopropelido. O indicador de decisão é o valor presente do lucro associado com o aumento de produtividade obtido com a adoção da irrigação. O método de simulação de Monte Carlos é utilizado para gerar a distribuição acumulada do valor presente para cada sistema de irrigação avaliado. Estas curvas permitem analisar a viabilidade econômica dos três sistemas de irrigação. De acordo com o primeiro grau de dominância estocástica, o sistema autopropelido foi a melhor alternativa com 95,7% de probabilidade de obtenção de valor presente positivo. A segunda melhor opção foi a microaspersão com 82,7% e a terceira escolha foi o gotejamento com 57,3%. UNITERMOS: viabilidade, simulação, sistemas de irrigação, dominância estocástica, citros.